Curved coating structures improve the durability of corrosion-resistant coatings on the heated surfaces of coal-fired boilers. (1st May 2023) - Huang, Yankai; Hu, Lina; Ahmat, Mutellip; Lei, Haijun
Abstract: The failure of the heating surface of coal-fired boilers remains a critical problem in rapidly peaking thermal power units. Applying a coating to the heating surface can mitigate this problem, but the coating lifetime is short. In this paper, we report a composite ceramic coating with a sinusoidal surface inspired by the fabrication of flexible electronic devices. Based on the elastic–plastic constitutive, heat conduction, and diffusion equations of the substrate material, we created a multi-field coupled numerical analysis model to identify the ideal sinusoidal surface structure. We then performed thermal cycling and molten salt corrosion experiments to assess the durability of the coating. Compared with the flat coating, the coating with a sinusoidal curved surface exhibited higher interfacial strength, reduced crack expansion, and improved corrosion resistance. These results provide a workable technical solution to prevent the failure of boiler heating surfaces in thermal power plant units under rapidly changing loads.